(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1923)
The pigments used on early Byzantine and early Celtic manuscripts are considered with particular reference to the difficulties involved in preparing ultramarine from lapiz lazuli. The Rosslyn Missal is believed to be of late thirteenth or early fourteenth century. The letters down the margin of the MS. are outlined in black, and are tinted with four pigments, vermilion, orpiment, ultramarine, and shell-fish purple. The Celtic psalter is thought to be of eleventh-century date. The pigments used are lead in place of vermilion as in the Lindisfarne Gospels, the Irish variety of orpiment, transparent copper-green, badly washed ultramarine, and shell-fish purple. The gold used on a single page consists of little rounded and kidney-shaped particles obtained as the fine gold dust from river gold.